SurfILE: An Open-Source Python Package for Surface Topography Analysis - Andrea Giura; Massimo Zucco; Luigi Ribotta (Metrology)
Surface metrology deals with inspecting surfaces and profiles by using contact or non-contact profilometers. In this field, the characterization of the dimensional, morphological, and texture parameters of samples as well as the assessment of metrological characteristics of measuring instruments are key issues. Manufacturers of instruments provide commercial software tools to analyze topography data. There are also freely available tools, including open-source options, that provide a variety of algorithms and methods. The rapid growth of investigations aimed at better understanding the effects of the microscale phenomena requires the improved traceable calibration of samples, the development of new methodologies and measuring techniques, and the specification of new mathematical models and processing techniques. In this work, we present SurfILE, the launch of an open-source Python project that provides various procedures and algorithms for topography analysis. The open-source software presented in this article is intended to be modular, expandable, and customizable.